Mental Health Status of Parental Caregivers of Special Needs Children in Puducherry - Philip Felix Priya; Ananda Balayogi Bhavanani; Meena Ramanathan; Karthick Subramanium; Sukanto Sarkar; Anandraj Lokeshmaran (Rambam Maimonides Medical Journal, 2025)
Background: Parental caregivers of children with special needs manage their child’s daily tasks, taking on responsibilities such as making health and financial decisions, assisting with routine activities, and ensuring their safety from self-harm. The level of a child’s disability determines the amount of time and effort a caregiver must invest, with higher disability levels meaning greater dependency and thus requiring greater support. While rewarding, caregiving may also be highly demanding. The parental caregiver’s physical and mental health can decline due to stress, potentially leading to anxiety and depression, and may worsen pre-existing conditions. This research aimed to provide insights into the psychological well-being of parental caregivers, shedding light on their challenges and needs for better support and intervention.